Pengaruh Likuiditas, Profitabilitas dan Leverage terhadap Return Saham pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2015-2018 - Merida; Ayubi Sidiq, Al (JOURNAL INTELEKTUAL, 2022)
Introduction/Main Objectives: The purpose of this study was to analyze the effect of liquidity, profitability, and leverage on stock returns. The population of this study is a food and beverage company that has an IDX license. Background Problems: Stock returns are used to assess the company's profit obtained from the investment made. There are several factors that affect this stock return, there are liquidity, profitability and leverage. Novelty: The samples taken for this study were several companies that reported their annual financial statements in 2015-2018. Research Methods: The analysis used in this study is multiple regression analysis The sampling technique used is purposive sampling of 25 different companies. Finding/Results: The results of the study using the calssical assumption test which shows that there is a transfer of classical assumptions indicate that the available data processed is eligible to be used for multiple linear regression models. Conclusion: The results showed that liquidity, profitability and leverage variables significantly have a positive influence on stock returns.